Adopsi Google Classroom Menggunakan Extended Technology Acceptance Model (EX-TAM) - Mohammad Mansyur Abidin (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
This study examines factors influencing the adoption of Google Classroom among students at private universities in East Java using the Extended Technology Acceptance Model (EX-TAM). The model integrates core TAM constructs and external variables including Social Influence, Motivation, Perceived Enjoyment, and Self-Efficacy. Data from 146 respondents were analyzed using LSR-SEM. Findings indicate that Perceived Ease of Use and Perceived Usefulness significantly influence Behavioral Intention, while Social Influence does not. Motivation and Self-Efficacy significantly affect Perceived Ease of Use, whereas Perceived Enjoyment does not. Perceived Ease of Use also significantly impacts Perceived Usefulness. These results highlight the importance of perceived ease of use, perceived usefulness, and self efficacy in encouraging the adoption of digital learning platforms.